Atividade física de trabalhadores de uma indústria moveleira de Antônio Prado RS - Marini, Tais Alegre (My University, 2022)
The objective of this study was to verify how the physical activity of the employees of a furniture industry in the city of Antônio Prado - RS occurs, having as specific objectives to verify how the physical activity of the employees occurs according to the sector in which they work in the company, to verify how the employees' physical activities according to employees' gender and to identify which type of physical exercise is most practiced by employees. The methods used were quantitative, descriptive and transversal. The sample included 61 company employees aged over 18 years. The instrument used was a Baecke physical activity level questionnaire (1982) adapted by Florindo L L (2004). The results showed that most employees (72.1%) practice physical exercises outside the work environment. In the workplace, employees in the production sector perform more activity and physical effort compared to the administrative sector. There is no significant difference in physical activity in the work environment or in employees' leisure time in relation to gender. The physical exercises most practiced by the research participants were the gym with 19.1%, followed by walking and soccer with 11.8%. [resumo fornecido pelo autor]
O objetivo deste estudo foi verificar como ocorre a atividade física dos funcionários de uma indústria moveleira da cidade de Antônio Prado - RS, tendo como objetivos específicos verificar como ocorre a atividade física dos funcionários conforme o setor em que atuam na empresa, verificar como ocorre a atividades física dos funcionários conforme o sexo dos funcionários e identificar qual a modalidade de exercício físico mais praticada pelos funcionários. Os métodos utilizados foram de caráter quantitativo, descritivo e transversal. A amostra contou com 61 funcionários da empresa com idade superior a 18 anos. O instrumento utilizado foi um questionário de nível de atividade física Baecke (1982) adaptado por Florindo et al (2004). Os resultados apontaram que os funcionários, em sua maioria (72,1%) praticam exercícios físicos fora do ambiente de trabalho. No local de trabalho, os funcionários do setor de produção realizam maior atividade e esforço físico comparado ao setor administrativo. Não há diferença significativa na atividade física no ambiente de trabalho nem no momento de lazer dos funcionários em relação ao sexo. Os exercícios físicos mais praticados pelos participantes da pesquisa foram academia com 19,1%, seguidos de caminhada e futebol com 11,8%. [resumo fornecido pelo autor]
Keywords: Educação física; Exercícios físicos; Trabalhadores - Antônio Prado (RS); Indústria de móveis